A Review of Districting Problems in Health Care - Yanık, Seda; Bozkaya, Burçin (Springer International Publishing, 2020)
In this chapter, we review the districting literature in the health care domain. Our goal is to provide the reader with the most relevant studies in the literature as well as a direction for future research. We classify the health care districting problems into three main areas: home care services, primary and secondary health care services, and emergency health care services. We first identify the special characteristics of these different areas. Then we present the modeling approaches, assumptions and solution methods for each of them. In general, we find that certain aspects and dimensions of health care service delivery, which we highlight in this chapter, lend themselves better to the design and implementation of districting-based approaches. As such, we limit our review mostly to studies that include traditional districting models and formulations as well as solution approaches. In closing, we discuss some gaps in the literature and provide directions for future areas of research.